Short-term clinical and radiological outcomes of treatment of acromioclavicular joint dislocations with the TightRope technique - Çepni, Şahin; Aydın, Mustafa (Journal of Surgery and Medicine, 2021)
Background/Aim: High-grade acromioclavicular joint injuries are usually treated surgically. However, there is still no consensus on which technique should be performed. We investigated the short-term clinical and radiological outcomes of the patients treated with the TightRope technique. Methods: In this retrospective cohort study, 15 patients (13 males and 2 females) who had an acromioclavicular joint injury and were treated with the TightRope technique between October 2015 and May 2019 were evaluated. The patients who had Rockwood type III (1 patient), type IV (8 patients), and type V (6 patients) injuries and had been followed up for at least 1 year were included in the study. At the final visits, the patients were evaluated functionally with VAS, DASH, and Constant scores, as well as radiologically by measuring the coracoclavicular distance on bilateral shoulder AP X-rays. Results: The mean duration of follow-up was 25.2 (5.6) months. Mean time to surgery was 3.0 (2.2) days and mean time to return to work was 8.8 (1.7) weeks. The coracoclavicular distance was 11.6 (2.1) mm on the affected side and 10.2 (0.8) mm in the other shoulder. Mean VAS, DASH, and Constant scores at the final visit were 1, 10, and 92, respectively. Conclusion: Use of the TightRope technique for the treatment of acromioclavicular dislocations might be effective like other methods that contribute to early regaining of range of motion of the shoulder joint, in addition to reduction of the dislocation.